Effective Thinking: An Active-Learning Course in Critical Thinking - Barry Leshowitz; Kristen Eignor DiCerbo; Scott Symington (Arizona State University, 2011)
This article describes a college course in critical thinking. Offered in the Psychology Department at Arizona State University, this active-learning course provides instruction in how to apply principles of (scientific) methodological reasoning and optimum decision making to problems faced in everyday-life situations. Students learn to evaluate statistical and scientific evidence, clarify personal and societal values, and anticipate the consequences of their actions in dealing with personally significant issues. Crime and punishment, societal acceptance of the gay lifestyle, alcohol abuse, and racial stereotypes comprise a partial list of topics addressed in the class. Using Internet links to recorded classroom discussions archived on the World Wide Web, the article provides qualitative support for a three-level model of critical thinking. This model attempts to account for the progression of methodological reasoning skills and related dispositions that takes place over the course of the semester.